Mean loads on vaulted canopy roofs - Natalini, Bruno (2013)
The vaulted canopy roof (VCR) is a widespread structure used in vast areas of South America, especially in parts of Argentina, Brazil and Paraguay. Information about the aerodynamics of VCRs is scarce in the literature, and it is restricted to mean load coefficients, which must be used in combination with the quasi-steady approach. Most of the existing data have been produced during the last decade in South America, but these data are not readily accessible because they were published in Spanish. This paper presents the results of mean wind load coefficients on VCRs obtained in boundary layer tunnel tests, and the aerodynamics of VCRs are discussed by taking into account the data produced during the last decade.